Crystal structure of chlorido-methanol-(N-(2-(oxy)-3-methoxybenzylidene)pyridine-4-carbohydrazonato-κ3O,N,O′)-(4-methylphenyl)methyl-tin(IV), C23H24ClN3O4Sn - Lee, See Mun *; Halcovitch, Nathan R.; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C23H24ClN3O4Sn, triclinic, P¯1 (no. 2), a=9.7536(2) Å, b=10.0755(2) Å, c=12.4215(3) Å, α=84.928(2)°, β=72.544(2)°, γ=74.382(2)°, V =1121.44(4) Å3, Z =2, Rgt(F)=0.021, wRref(F2)=0.054, T =100(2) K.